Pengelolaan Pasar Blante Untuk Meningkatkan Perekonomian Masyarakat di Kecamatan Tompaso Kabupaten Minahasa - Magdalena Tuwo; Welson Yappi Rompas; Rully Mambo (JURNAL ADMINISTRASI PUBLIK, 2023)
ABSRACK This study aims to find out how blante market management in improving the community's economy in Tompaso District, Minahasa Regency. This research uses a qualitative descriptive research type. Data collection techniques used are observation, interviews, and documentation. The results of this study indicate that the management of the blante market is not going well, the organization of the blante market is not clear in the Tompaso sub-district government program, there are no fees in the blante market because it does not run efficiently. important role for society. This is seen in terms of planning, organizing, actuating and controlling. Keywords: Blunt Market, Community, Barter.